Cow Math—Using Weaning Weight to Estimate Cowherd Productivity - Phillip Lancaster; John Arthington (EDIS)
“You can’t get where you’re going unless you know where you are.” The ability to measure performance is a key component in all beef cow operations, and measuring production efficiency is becoming increasingly important. Regardless of size, producers must be able to identify the current status of their operation in order to make adjustments toward improvement. Identifying and culling the cows within the herd that are less efficient at producing a weaned calf in the environment and management system used on the ranch can be a powerful tool to improve the revised herd. This 8-page fact sheet was written by Phillip Lancaster and John Arthington, and published by the UF Department of Animal Science, April 2014.